2007
DOI: 10.1063/1.2446286
|View full text |Cite
|
Sign up to set email alerts
|

Efficient K-shell x-ray sources produced with titanium foils

Abstract: The conversion efficiency of titanium K-shell x rays is experimentally investigated in the Shenguang II laser facility. For comparison, Ti foils with the thickness of 3.5 and 5.8μm are irradiated under the same laser condition. The conversion efficiency with the thinner foils reaches about 3.5% and is about two times of that obtained with the thicker foils. The experiments show that the enhancement of the conversion efficiency should be due to the larger size of hot underdense plasmas generated with the thinne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Most of the articles concerning this issue concentrate on the influence of the laser intensity (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b;Dunn et al, 1995;Kodama et al, 1986), the atomic number (Kauffman, 1991;Mattews et al, 1983;Workman & Kyrala, 2001a, 2001bDunn et al, 1995;Ruggles et al, 2003;Yaakobi et al, 1981;Kodama et al, 1986), and the initial density of the target (Back et al, 2001(Back et al, , 2003Fiedorowicz, 2005;Fournier et al, 2004Fournier et al, , 2006Kodama et al, 1987;Teubner et al, 1991;Pelletier et al, 1997;Girard et al, 2005Girard et al, , 2004Primout, 2005). We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008. We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Most of the articles concerning this issue concentrate on the influence of the laser intensity (Mattews et al, 1983;Workman et al, 2003;Workman & Kyrala, 2001a, 2001bRiley et al, 2002b;Dunn et al, 1995;Kodama et al, 1986), the atomic number (Kauffman, 1991;Mattews et al, 1983;Workman & Kyrala, 2001a, 2001bDunn et al, 1995;Ruggles et al, 2003;Yaakobi et al, 1981;Kodama et al, 1986), and the initial density of the target (Back et al, 2001(Back et al, , 2003Fiedorowicz, 2005;Fournier et al, 2004Fournier et al, , 2006Kodama et al, 1987;Teubner et al, 1991;Pelletier et al, 1997;Girard et al, 2005Girard et al, , 2004Primout, 2005). We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008. We also found that by using a long pulse laser, the laser focus spot size and the thickness of the thinfoil target (the thickness is comparable to the burn through length, which is the initial target thickness that the laser beam can transmit through the entire plasma region with little absorption at the end of the laser pulse) can change the conversion of multi-keV K-shell X-ray emission significantly (Hu et al, 2007(Hu et al, , 2008.…”
Section: Introductionmentioning
confidence: 84%
“…The diagnostic system is similar to that in our previous work (Hu et al, 2007(Hu et al, , 2008. A set of X-ray diodes (XRDs) at different viewing angles are used to give the X-ray flux and the angular distribution with temporal resolution of 250 ps and relative uncertainty of +30%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Recently the additional ͑ninth͒ laser beam, which can also deliver 70-150 ps short pulse besides the nanosecond long pulse, was established on the Shenguang II laser facility. [19][20][21] The ninth laser beam could be used to generate shorter backlighter compared with the previous experiments. 7,[14][15][16][17] The shorter backlighter could provide better temporal resolution.…”
Section: Introductionmentioning
confidence: 97%
“…However, it was difficult to obtain a clear image of the plasma hydrodynamic movement because the spectrum of the self-backlighter source used then was broad-band. In 2009, a new experiment was performed on the SG-II laser facility using laser-irradiated Ti disk to generate 2-5 keV X-ray as the intense backlighter source, 15 and a quantitative diagnostic method of plasma movement in the small hole was established. 16 In Sec.…”
mentioning
confidence: 99%